Neural Responses to the Implicit Processing of Emotional Facial Expressions in Binge Drinking. (20th October 2020) - Lannoy, Séverine; Dricot, Laurence; Benzerouk, Farid; Portefaix, Christophe; Barrière, Sarah; Quaglino, Véronique; Naassila, Mickaël; Kaladjian, Arthur; Gierski, Fabien
Abstract: Aims: Emotional processing is a crucial ability in human and impairments in the processing of emotions are considered as transdiagnostic processes in psychopathology. In alcohol use disorder, numerous studies have investigated emotional processing and showed emotional deficits related to the perpetuation of alcohol use. Recent studies have also explored this topic in binge drinking, but few studies are available. In this paper, we explored whether emotional difficulties in binge drinking may be extended to implicit emotion processing. Methods: We compared 39 binge drinkers (BD) and 40 non-binge drinkers who performed a gender categorization task while faces represented emotional expressions of anger, fear, happiness and sadness. Emotional brain responses were assessed thanks to functional magnetic resonance imaging. Emotional versus non-emotional conditions were first contrasted in the whole sample and groups were then compared. Results: Emotional condition led to differential activations than non-emotional condition, supporting the validity of the paradigm. Regarding group comparisons, BD exhibited higher activations in the left posterior cerebellum (anger processing) and the right anterior cingulate (fear processing) as well as lower activations in the left insula (happiness), the right post-central gyrus, the right cingulate gyrus and the right medial frontal gyrus (sadness processing). Conclusions: Beyond emotional identification, BD presented differential brain responses following the implicit processing of emotions. Emotional difficulties in binge drinking might be related to a more automatic/unconscious processing of emotions. Abstract : Short Summary: Emotional processing has been indexed as impaired in binge drinking. We explored whether emotional difficulties may be extended to the implicit processing of emotions. Brain responses of binge drinkers (BD) and controls were evaluated thanks to functional magnetic resonance imaging during a gender categorization task presenting emotional faces. BD exhibited specific brain activations.